2023
DOI: 10.21203/rs.3.rs-2362342/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GDF-15 and Hepciden as a therapeutic target for anemia in chronic kidney disease

Abstract: Background Anaemia is a common presenting feature among patients with chronic kidney disease (CKD) and associated with poor clinical outcomes. We evaluated the diagnostic validity of growth differentiation factor-15 (GDF-15) and hepcidin as it is not clear if they are useful as a biomarkers of anaemia among non-dialysis CKD egyptian patients. Method An analytical cross-sectional study was conducted among non-dialysis CKD patients (n = 60) and apparently healthy controls (n = 28) at Minia University maternity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…A recent study of patients with CKD that examined the association between anemia, GDF-15, and hepcidin found significant correlations between hepcidin levels and iron and CRP and significant correlations between serum GDF-15 and Hb levels, ferritin, iron, and CRP. In that study, multivariate logistic regression analysis found that Hb (β=-0.34), GDF-15 (β=-0.3), and hepcidin (β=-0.26) were predictors of anemia in patients with CKD [26]. Therefore, an increased GDF-15 level as well as iron deficiency might be useful markers for the screening of anemia, which is common in older adults.…”
Section: Relevance Of Gdf-15 and Hepcidin For The Management And Trea...mentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study of patients with CKD that examined the association between anemia, GDF-15, and hepcidin found significant correlations between hepcidin levels and iron and CRP and significant correlations between serum GDF-15 and Hb levels, ferritin, iron, and CRP. In that study, multivariate logistic regression analysis found that Hb (β=-0.34), GDF-15 (β=-0.3), and hepcidin (β=-0.26) were predictors of anemia in patients with CKD [26]. Therefore, an increased GDF-15 level as well as iron deficiency might be useful markers for the screening of anemia, which is common in older adults.…”
Section: Relevance Of Gdf-15 and Hepcidin For The Management And Trea...mentioning
confidence: 89%
“…The association between GDF-15 and hepcidin remains unclear. A significant association between GDF-15 and hepcidin has not been reported for patients with inflammatory and iron-deficiency anemia [11] or with CKD [26]. GDF-15 was reported to be positively correlated with hepcidin in non-anemic patients [29].…”
Section: Relevance Of Gdf-15 and Hepcidin For The Management And Trea...mentioning
confidence: 93%